SGLT2-inhibitor and DPP-4 inhibitor improve brain function via attenuating mitochondrial dysfunction, insulin resistance, inflammation, and apoptosis in HFD-induced obese rats - Sa-nguanmoo P. (2017)
© 2017 Elsevier Inc. Dipeptidyl peptidase-4 inhibitor (vildagliptin) has been shown to exert beneficial effects on insulin sensitivity and neuroprotection in obese-insulin resistance. Recent studies demonstrated the neuroprotection of the sodium-glucose co-transporter 2 inhibitor (dapagliflozin) in diabetes. However, the comparative effects of both drugs and a combination of two drugs on metabolic dysfunction and brain dysfunction impaired by the obese-insulin resistance have never been investigated. Forty male Wistar rats were divided into two groups, and received either a normal-diet (ND, n = 8) or a high-fat diet (HFD, n = 32) for 16 weeks. At week 13, the HFD-fed rats were divided into four subgroups (n = 8/subgroup) to receive either a vehicle, vildagliptin (3 mg/kg/day) dapagliflozin (1 mg/kg/day) or combined drugs for four weeks. ND rats were given a vehicle for four weeks. Metabolic parameters and brain function were investigated. The results demonstrated that HFD rats developed obese-insulin resistance and cognitive decline. Dapagliflozin had greater efficacy on improved peripheral insulin sensitivity and reduced weight gain than vildagliptin. Single therapy resulted in equally improved brain mitochondrial function, insulin signaling, apoptosis and prevented cognitive decline. However, only dapagliflozin improved hippocampal synaptic plasticity. A combination of the drugs had greater efficacy in improving brain insulin sensitivity and reducing brain oxidative stress than the single drug therapy. These findings suggested that dapagliflozin and vildagliptin equally prevented cognitive decline in the obese-insulin resistance, possibly through some similar mechanisms. Dapagliflozin had greater efficacy than vildagliptin for preserving synaptic plasticity, thus combined drugs could be the best therapeutic approach for neuroprotection in the obese-insulin resistance.